Earthquake and Tsunami Disaster Risk Mapping and Mitigation Strategy in Torok Aik Belek Hamlet: Community-Based Approach - Syamsuddin Syamsuddin; Rahmatun Inayah; Ika Umratul Asni Aminy; Adella Ulyandana Jayatri; Kormil Saputra; Suhayat Minardi; Alfina Taurida Alaydrus; Dian Wijaya Kurniawidi (Future Tecno-Science Publisher, 2025)
Indonesia has a high level of geological disaster threat due to its location at the meeting point of three tectonic plates, making coastal areas, such as Lombok Island, very vulnerable to earthquakes and tsunamis. Although Lombok has a history of earthquakes (2018) and tsunamis (1977), initial observations in Torok Aik Belek Hamlet, South Lombok, show that community awareness and preparedness for disaster mitigation are still low, exacerbated by unverified information on social media and the perception of underestimating potential hazards. This study aims to conduct participatory earthquake and tsunami risk mapping in Torok Aik Belek Hamlet and develop community-based mitigation strategies. The implementation methods include initial assessment, coordination with BMKG, presentation of materials, interactive counseling, and community empowerment as a disaster preparedness team. The results of the activities show clear identification of disaster-prone locations (for example, residential areas near the coast and concrete buildings) and vulnerable groups. Utilization of local potential, such as hills as evacuation routes and disaster-resilient village status, is the basis for developing disaster mitigation strategies. The formation of a local community in Torok Aik Belek Hamlet involving residents and members of the Disaster Resilient Village is a crucial step. It is hoped that this effort can significantly increase the preparedness of the Torok Aik Belek Hamlet community and contribute to an adaptive and sustainable community-based mitigation development model.